Escravidão e liberdade no Piauí oitocentista: alforrias, reescravização e escravidão ilegal de pessoas livres (1850-1888) - Costa, Francisca Raquel da (2017)
In order to break with analyzes that see a soft slavery in Piauí and also break with the vision of a benevolent elite, supposedly, due to the almost inexistence of slave labor in the region that was economically based on cattle ranching. Thus, this thesis demonstrates the struggles undertaken by the slaves, as well as the freedmen and free people of color to achieve and maintain freedom, even during the permanence of the slave regime in the province of Piauí, evidencing the fragility of its effectiveness. The objectives of this work are: to discuss the question of freedom and the various ways the slaves had to reach it, and the freedmen to keep it in the slave-owning Piauí of the nineteenth century; to emphasize the experiences of building this freedom, the thin line between this freedom and the slavery and to highlight the challenges encountered by these subjects. To this end, diverse historical sources were used to reconstruct the trajectories of slave-owners, slaves and freedmen who experienced the province‘s day-to-day life of slavery in the second half of the nineteenth century. We emphasize that the experiences of these social agents were related to economic, social and cultural issues, as well as to the transformations that occurred in Piauí in that period such as: the lack of an economic structure; the intense flow of slaves displaced through interprovincial trafficking due to the closing of the slave trade from Africa to Brazil, especially in the dry season of 1877-1879; and finally the promulgation of the Free Womb Law of 1871, which sought to legalize the attainment of liberty by captives through various legal devices, redefining and shaping the tense social relations woven between slave-owners and slaves.